Hypoparathyroidism-retardation-dysmorphism syndrome—Clinical insights from a large longitudinal cohort in a single medical center - David, Odeya; Agur, Rotem; Novoa, Rosa; Shaki, David; Walker, Dganit; Carmon, Lior; Eskin-Schwartz, Marina; Birk, Ohad S.; Ling, Galina; Schreiber, Ruth; Loewenthal, Neta; Haim, Alon; et al. (Frontiers in Pediatrics, 2022)
Background: Hypoparathyroidism, retardation, and dysmorphism (HRD) Syndrome is a rare syndrome composed of hypoparathyroidism, retardation of both growth and development, and distinctive dysmorphic features. Here, we describe the long-term morbidity and mortality in a large cohort of HRD patients and suggest recommendations for follow up and treatment. Methods: Medical records of 63 HRD syndrome patients who were followed at Soroka Medical Center during 1989–2019 were reviewed retrospectively. Information regarding demographics, medical complications, laboratory findings, and imaging studies was collected. Results: The mortality rate was 52%. The main causes of death were infectious diseases including pneumonia, septic shock, and meningitis. Multiple comorbidities were found including brain anomalies in 90% of examined patients (basal ganglia calcifications, tightening of corpus callosum, Chiari malformation, hydrocephalous, and brain atrophy), seizures in 62%, nephrocalcinosis and/or nephrolithiasis in 47%, multiple eye anomalies were recorded in 40%, bowel obstructions in 9.5%, and variable expression of both conductive and senso-neural hearing loss was documented in 9.5%. Conclusion: HRD is a severe multisystem disease. Active surveillance is indicated to prevent and treat complications associated with this rare syndrome.